Direct Synthesis of Photosensitizable Bacterial Cellulose as Engineered Living Material for Skin Wound Repair. Issue 13 (18th February 2022) - Liu, Xingang; Wu, Min; Wang, Meng; Hu, Qida; Liu, Jingjing; Duan, Yukun; Liu, Bin
Abstract: Living materials based on bacterial cellulose (BC) represent a natural and promising candidate for wound dressing. Both physical adsorption and chemical methods have been applied to BC for realizing antibacterial function. However, effective and long‐lasting incorporation of bactericidal moieties to BC remains challenging. Herein, a Komagataeibacter sucrofermentans ‐based direct synthetic method to fabricate photosensitizer‐grafted BC through in situ bacterial metabolism in the presence of TPEPy‐modified glucose is explored. The results verify that the direct biosynthesis method is efficient and convenient to endow BC with outstanding fluorescence and light‐triggered photodynamic bactericidal activity for skin wound repair. This work presents a new approach to fabricate eco‐friendly and active wound dressing with light‐controlled bactericidal activity by microbial metabolism. The successful modification of the glucose carbon source of microorganisms also offers insights for biosyntheses of other living materials through microbial metabolism. Abstract : Photosensitizable bacterial cellulose is obtained via direct microbial metabolism biosynthesis for wound repair in vivo with effective antibacterial functions.